Kako natančna je lahko transkripcija - Krajnc Ivič, Mira (Slavia Centralis, 2020)
How Precise Can a Transcription Be?The article attempts to show how a message of a direct dialogue gets its (illocutionary) force as the result of the interplay of linguistic, semi-linguistic and non-linguistic activities of the participant. It is also trying to show that researchers' difficulties are the consequences of his or her wish to transcribe a dialogue perfectly, because only a perfect and theoretically non-neutral transcription can be used for several different purposes.
Keywords: discourse; conversation; direct dialogue; transcription; prosody